Analisis Lagu Karo “Erkata Bedil” Karya Djaga Sembiriing Depari Menggunakan Pendekatan Ekspresif - Puspita, Diana; Reza Pahlevi Ginting (Lembaga Bale Literasi, 2024)
A song is a work of art which is the result of the relationship between sound art and language art. Songs are created to convey messages and express what the songwriter feels and sees. In this increasingly developing era, many young Karo people are leaving behind their cultural heritage such as dance, music, especially traditional songs from the land of Karo. Therefore, in this research the author anan carried out an analysis of one of the Karo struggle songs entitled